Consider the following sequence -
2 1 , 3 5 , 8 1 1 , 1 9 2 7 ⋯
Now, if T n is the nth term of this sequence and N ( T n ) is the numerator of the term and D ( T n ) is the denominator of the term, then find digit sum ⎝ ⎛ ( n → ∞ lim ( T n ) ) 2 N ( T 1 7 ) + N ( T 2 9 ) − D ( T 1 7 ) − D ( T 2 9 ) ⎠ ⎞
This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try
refreshing the page, (b) enabling javascript if it is disabled on your browser and,
finally, (c)
loading the
non-javascript version of this page
. We're sorry about the hassle.
There may be some things which you might not have understood as I have written the solution in a hurry so you can ask me here in personal.
Log in to reply
Are you still an active brilliant user? I have a thought or two on this problem but I will elaborate if I hear from you
Problem Loading...
Note Loading...
Set Loading...
First of all, this is not an original problem, it is taken from some test and then edited a little bit.
After looking at the sequence, the only sequence which can(I guess) come in mind -
D ( T n ) = D ( T n − 1 ) + N ( T n − 1 )
N ( T n ) = D ( T n ) + D ( T n − 1 )
But still, if there is any more series coming up, then please let me know I will provide this thing in the question only.
Let's just simply replace D ( T n ) by q n and N ( T n ) by p n .
q n = q n − 1 + p n − 1
p n = 2 q n − 1 + p n − 1
Now, q n = 3 q n − 2 + 2 p n − 2
q n = 7 q n − 3 + 5 p n − 3
and so on, so we can write - q n = a k q n − k + b k p n − k
As we can easily see, there is a recurrence going on in a i s and which is that -
a k = 2 a k − 1 + a k − 2 with a 1 = 1 , a 0 = 1
And hence, the equation we will get is x 2 = 2 x + 1
As we will bash a little bit more, we get a k = 2 1 ( ( 1 + 2 ) k + ( 1 − 2 ) k )
Also, b k = b k − 1 + a k − 1
= 2 1 ( ( 1 + 2 ) k − 1 + ( 1 − 2 ) k − 1 ) + b k − 1
= 2 1 ( ( 1 + 2 ) k − 1 + ( 1 − 2 ) k − 1 ) + 2 1 ( ( 1 + 2 ) k − 2 + ( 1 − 2 ) k − 2 ) + b k − 2
And so on till b 0 = 0 ,
= r = 1 ∑ k 2 1 ( ( 1 + 2 ) k − r + ( 1 − 2 ) k − r )
= 2 2 ( 1 + 2 ) k − 1 − ( 1 − 2 ) k − 1
Now, just plugging values and a little bashing, we get
q n = 2 2 ( 2 2 + 1 ) ( ( 1 + 2 ) n − 1 ) + ( 2 2 − 1 ) ( ( 1 − 2 ) n − 1 ) [Considering values of q 1 and p 1 ]
Well, let's move to p n which is defined as -
p n = 2 q n − 1 + p n − 1
p n = 2 ( 2 2 + 1 ) ( ( 1 + 2 ) n − 1 ) + ( 2 2 − 1 ) ( ( 1 − 2 ) n − 1 ) + p n − 1
And as we know that p 1 = 1 , we can bash a little bit again
p n = 2 2 + ( 2 2 + 1 ) ( ( 1 + 2 ) n − 1 − 1 ) + ( 2 2 − 1 ) ( ( 1 − 2 ) n − 1 − 1 )
We have got equations of both - numerator as well as denominator and now comes the terminator which is just plugging in values.
p 2 9 = 9 9 9 3 3 1 5 0 3 0 5
p 1 7 = 2 5 4 9 1 8 5
q 2 9 = 7 0 6 6 3 4 0 8 2 4 6
q 1 7 = 1 8 0 2 5 4 6
l i m n − > ∞ ( T n ) = 2
Doing the final thing we get the answer as -
4 5